Self-efficacy, learning motivation, learning environment and its effect on online learning outcomes - Masrun Masrun; Rusdinal Rusdinal (Universitas Negeri Yogyakarta, 2022)
This study aimed to analyze e students’ psychological factor, namely self-efficacy, learning motivation and learning environments on the results of online physical education learning during Covid-19 at Senior High School in Padang, West Sumatera. This study used a quantitative method using a path analysis approach, with structural equations to find out the causality of the dimensions of self-efficacy, motivation, directly on learning outcomes of physical education, or indirectly through the learning environment. The data collection was carried out using a survey technique to 160 high school students in Padang and analyzed using descriptive statistics. The results show that the power of direct influence the self-efficacy and learning motivation and significantly effect their online learning through the learning environment. It also has an impact on learning outcomes. When the teaching and learning process must be carried out through an online system, it is necessary to make improvements to various models and learning designs, so that the learning process is avoided from negative influences that can reduce student learning outcomes